PENGARUH DAYA TARIK FISIK DAN KEINDAHAN LINGKUNGAN TERHADAP KEPUASAN PELANGGAN PADA PRODUK PERUMAHAN BUANA CENTRAL PARK DI KOTA BATAM - Sinaga, Lina; Syaifullah, Syaifullah (LPPM Universitas Putera Batam, 2019)
Technological developments are increasingly growing rapidly, taking factors decisions made by customers or consumers are influenced by personal traits. environment to customer satisfaction in Buana Central Park housing products. This research aims to determine the effect of physical attractiveness, and the beauty of the population in this research were all customers of PT Buana Cipta Propertindo in Batam City, who were once purchased Buana Central Park products, samples used in this research amounted to 100 people with saturated sampling techniques. This type of research is quantitative. This research uses multiple linear regression analysis. The results of this research shows that the physical attractiveness and beauty of the environment are influential significant to customer satisfaction. Data quality test used in this research using validity and reliability tests that show that the indicators are used valid to measure existing variables. In the classical assumption test, the data regression model normal distribution, free of multicellularity and heteroscedasticity does not occur. Results the research shows that partially (T test) variable physical attractiveness and beauty environment has a positive and significant effect on customer satisfaction in purchasing Buana Central Park housing products amounted to 2,458 and 3,339. then, simultaneously (test F) variable physical attractiveness and beauty of a positive and influential environmen. Significance of customer satisfaction in the purchase of housing products was 166,023. And the coefficient of adjusted is 20.7%, which means the purchase decisioncan be explained by the variable physical attractiveness and beauty of the environment while the rest 79.3% was affected by other variables not examined in this research. From the results of the research concluded that physical attractiveness and the beauty of the environment have a positive effect on customer satisfaction in the housing company Buana Central Park in Batam City.